Therapeutic Administration of Broadly Neutralizing FI6 Antibody Reveals Lack of Interaction Between Human IgG1 and Pig Fc Receptors - Morgan, Sophie B.; Holzer, Barbara; Hemmink, Johanneke D.; Salguero, Francisco J.; Schwartz, John C.; Agatic, Gloria; Cameroni, Elisabetta; Guarino, Barbara; Porter, Emily; Rijal, Pramila; Townsend, Alain; Charleston, Bryan; et al. (Frontiers in Immunology, 2018)
Influenza virus infection is a significant global health threat. Because of the lack of cross protective universal vaccines, short time window during which antivirals are effective and drug resistance, new therapeutic anti-influenza strategies are required. Broadly cross-protective antibodies that target conserved sites in the hemagglutinin (HA) stem region, have been proposed as therapeutic agents. FI6 is the first proven such monoclonal antibody to bind to H1-H16 and is protective in mice and ferrets. Multiple studies have shown that Fc-dependent mechanisms are essential for FI6 in vivo efficacy. Here we show that therapeutic administration of FI6 either intravenously or by aerosol to pigs did not reduce viral load in nasal swabs or broncho-alveolar lavage, but aerosol delivery of FI6 reduced gross pathology significantly. We demonstrate that pig Fc receptors do not bind human IgG1 and that FI6 did not mediate antibody dependent cytotoxicity (ADCC) with pig PBMC, confirming that ADCC is an important mechanism of protection by anti-stem antibodies in vivo. Enhanced respiratory disease, which has been associated in pigs with cross-reactive non-neutralising anti-HA antibodies, did not occur after FI6 administration. Our results also show that in vitro neutralizing antibody responses are not a robust correlate of protection for the control of influenza infection and pathology in a natural host model.